Planning on tourism: an important issue for the sustainable and regional development of Boyacá (2013)
This article refers to some relevant information concerning tourism politics a regional and national level, based on the great importance that this activity has acquired in the economic and social development of the state of Boyacá and through the country. In this research work we can observe some failures in which tourism development has fallen, doing some special emphasis on the weak processes of planning and integrated management that really lead to a tourist sustainable development and for this reason it becomes necessary to issue clear actions through projects and clearly define programs that help to improve the quality of life of the local community, being also necessary to deepen in what these tourism planning processes really involve and must be framed under laws of sustainable development. This previous reflection lead us to show how the Pedagogical and Technological University of Colombia supports in a significant way the region and contributes to the qualification of the regional and local human resources starting from university vision and mission view and also from a relevant academic offer which is its Specialization in Planning of the Sustainable Tourism.